Characterization of Nicotine Salts in 23 Electronic Cigarette Refill Liquids. Issue 7 (10th December 2019) - Harvanko, Arit M; Havel, Christopher M; Jacob, Peyton; Benowitz, Neal L
Abstract: Introduction: Many electronic cigarette manufacturers have begun offering liquids containing "nicotine salts, " which are formed when an acid is mixed in a solution with free-base nicotine. Type of salt could play a significant role in the abuse liability of electronic cigarette liquids. As a first step to understanding nicotine salts, this study sought to identify the types of acids present in 23 commercially available electronic cigarette liquids. Aims and Methods: Twenty-three electronic cigarette liquids advertised as containing nicotine salts were purchased for analysis. These liquids were tested for the presence of 11 different organic acids that were deemed likely to be used in a nicotine salt formulation. Liquids were analyzed using a combination of liquid chromatography–mass spectrometry and gas chromatography–mass spectrometry methods, then compared to authentic acid standards for identification. Results: Six of the 11 possible acids were identified in the liquids, from most to least common: lactic, benzoic, levulinic, salicyclic, malic, and tartaric acid. Acid(s) could not be identified in one of the liquids. Though most liquids contained only one type, three of the liquids contained multiple acids. Conclusions: These data demonstrate that several types of salts/acids are currently being used in electronic cigarette liquids. The type and concentration of salt(s) used in these liquids may differentially alter sensations in the throat and upper airway, and overall pharmacology of the aerosols by altering liquid pH and from flavor and sensory characteristics of the acids themselves. Implications: This study demonstrates that at least six different types of acids are being used to create the nicotine salts in electronic cigarette liquids, with the acids lactic, benzoic, and levulinic being the most frequently identified. Identification of these acids can serve as the foundation for future research to determine if type of nicotine salt alters pharmacological and toxicological effects of electronic cigarettes.